Does central bank communication signal future monetary policy? The case of the ECB - Hamza Bennani; Nicolas Fanta; Pavel Gertler; Roman Horváth (Charles University in Prague, Institute of Economic Studies (IES), 2019)
We examine the European Central Bank's ad-hoc communication and explore how it informs future monetary policy decisions. Using the rich dataset of the intermeeting verbal communication among the members of the European Central Bank's Governing Council between 2008 and 2014, we construct a measure of communication assessing its inclination towards easing, tightening or maintaining the monetary policy stance. We find that this measure provides useful additional information about future monetary policy decisions, even when we control for market-based interest rate expectations and lagged decisions. Our results also suggest that, in particular, communication shortly before monetary policy meetings, related to unconventional measures and/or by the ECB President explain the future ECB rate changes well. Overall, these results point to the importance of transparency in understanding the future course of monetary policy.
Keywords: E52; E58; 330; Central bank communication; ECB; monetary policy